Anodic and Cathodic preparation of MnO2/Co2O3 Composite Electrode Anodes for Electro-Oxidation of Phenol - Ahmed, Yamama A.; Salman, Rasha H.; Kandemirli, Fatma (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The economical and highly performed anode material is the critical factor affecting the efficiency of electro-oxidation toward organics. The present study aimed to detect the best conditions to prepare Mn-Co oxide composite anode for the electro-oxidation of phenol. Deposition of Mn-Co oxide onto graphite substrate was investigated at 25, 30, and 35 mA/cm2 to detect the best conditions for deposition. The structure and the crystal size of the Mn-Co oxide composite electrode were examined by using an X-Ray diffractometer (XRD), the morphological properties of the prepared electrode were studied by scanning electron microscopy (SEM) and Atomic force microscopy (AFM) techniques, and the chemical composition of the various deposited oxide was characterized by energy dispersive X-ray spectroscopy (EDX). The study also highlighted the effect of current density (40, 60, and 80 mA/cm2), pH (3, 4, and 5), and the concentration of NaCl (1, 1.5, and 2 g/l) on the anodic electro-oxidation of phenol was investigated. The results revealed that the composite anodes are successfully prepared galvanostatically by anodic and cathodic deposition. In addition, the current density of 25 mA/cm2 gave the best cathodic deposition performance. The removal efficiency of phenol and other by-products increased as the current density and the concentration of NaCl in the electrolyte increased, while it decreased as the pH increased. The prepared composite electrode gave high COD removal efficiency (98.769 %) at the current density of 80 mA/cm2, pH= 3, NaCl conc. of 2 g/L within 3 h.